Inovasi Pemanfaatan Keong Mas sebagai Bio-ZPT dan Bioaktivator berbasis PGPR di Desa Binangga Kabupaten Sigi Sulawesi Tengah - Kasman Jaya; Sri Sudewi; Hasmari Noer; Ratnawati Ratnawati; Abdul Rahim Saleh; Marliyah Marliyah (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
The Nosarara Farmers Group in Binangga Village, Marawola District, often faces challenges in the sustainability of rice productivity, namely attacks by golden apple snails (Pomacea canaliculata). Golden apple snails have the potential to be converted into high-value resources, as bio-PGRs and bioactivators in increasing rice plant productivity. The purpose of this Community Service (PkM) activity is to provide education, understanding, and skills to rice farmer groups in Binangga Village. This activity was carried out from September to October 2024 in Binangga Village, Marawola District, Sigi Regency, Central Sulawesi. The PRA (Participatory Rural Appraisal) Approach method was used in this activity to collect, analyze, and use information about community conditions and needs in a participatory manner. PRA prioritizes active community involvement in development and problem-solving with partners. The stages of the activities carried out began with preparation by coordinating with farmer groups and agricultural extension workers, socialization/extension activities, training and demonstrations, and evaluation of activities through monitoring. The results of the Community Service Program (PKM) activities showed an increase in farmers' understanding and skills, with 95% of farmer group members actively engaging in discussions and Q&A sessions through outreach, training, and field demonstrations. Farmer groups were highly enthusiastic about adopting new technologies, demonstrating the program's potential for sustainability in the future.